O13 Remission and LLDAS as a target for pregnancy planning in SLE?. (23rd March 2020) - Zucchi, Dina; Tani, Chiara; Monacci, Francesca; Elefante, Elena; Carli, Linda; Stagnaro, Chiara; Parma, Alice; Choi, May; Ferro, Francesco; Signorini, Viola; Gori, Sabrina; Strigini, Francesca; et al.
Abstract : Background: The attainment of remission and low disease activity (LLDAS) in SLE is associated with better outcomes. This study was aimed to test whether disease remission and LLDAS at the beginning of pregnancy are associated with better pregnancy outcomes. Methods: A total of 85 pregnancies in 61 SLE patients prospectively followed at a single center were considered; 10 pregnancies ended in spontaneous abortion during the first trimester and were excluded from the analysis. Definitions of remission (according to DORIS criteria) and LLDAS were applied at the first pregnancy visit (7–8 weeks of gestational age). Disease flare was defined according to the SELENA-SLEDAI flare index. Obstetric complications included preterm prelabour rupture of membranes, preeclampsia, preterm delivery, SGA infant, IUGR, intrauterine fetal death (IUFD) and gestational diabetes. Results: Characteristics of the cohort are detailed in table 1 . In twenty-one cases (28%) we observed flare during pregnancy or puerperium. Two severe flares and 19 mild-moderate flares were recorded. Obstetric complications were observed in 31 cases (41%). The risk of disease flare during pregnancy was significantly lower in patients in LLDAS at the beginning of pregnancy with respect to active patients (OR 12.47, p<0.02). Patients in LLDAS but not remission showed an increased risk of flare with respect to remitted patients (p<0.001) while no significant differences were found between patients in clinical versus complete remission. No associations were found between disease status at the beginning of pregnancy and obstetric complications. Conclusions: These data confirm that disease remission is one important predictor of pregnancy outcomes in SLE. While serology seems not to have a substantial role, a residual disease activity at conception might impact on pregnancy outcomes. Available definitions of remission and LLDAS could be valid treatment targets in the family planning perspective.